EXPLORING CRITICAL THINKING ACTIVITIES IN LISTENING COMPREHENSION EXERCISES - Sulistyani, Sulistyani; Khoiriyah, Khoiriyah; Wicaksono, Agung; Aji, Mahendra Puji Permana; Sardanto, Rino (Universitas Muhammadiyah Metro, 2023)
This study identifies the critical thinking activities employed in listening comprehension exercises and the way the activities facilitate students' listening comprehension. The study employs content analysis to explore integrating critical thinking activities in listening comprehension exercises. The study involves the listening exercise source, namely a textbook entitled Real Listening and Speakingoye Three by Miles Craven. The result of the study shows that critical thinking activities include identifying the situation and the factors that may influence it, locating the basis for the research that is presented to understand the big picture, learning how to avoid personal biases, and